Exercise Motivation and Processes of Change in Community-Dwelling Older Persons - 曾月霞(Yueh-Hsia Tseng); 趙叔蘋(Shwu-Pyn Jaw); 林姿利(Tzu-Li Lin); 何啟中(Chi-Chung Ho) (The Journal of Nursing Research, 2003)
Although exercise is important for the health of older persons, many older persons fail to participate in exercise. Knowledge and skills about changing exercise behavior is needed for health professionals to develop appropriate interventions to engage older persons in exercise. The purpose of this study was to determine how exercise processes of change were used by community-dwelling older persons to engage in exercise. A cross-sectional correlational design was employed. Cluster sampling was used to obtain potential subjects. A sample of 167 older persons participated in the study. The age of the participants ranged from 65 to 89 years (M = 73.7, SD = 6.14). Each participant was interviewed face-to-face with the investigator reading the questions and marking the answers on the Exercise Stages of Change Questionnaire and the Exercise Processes of Change Questionnaire. The results revealed that half of the older persons were underactive or inactive. One-way ANOVAs and Scheffe post-hoc analyses revealed that 10 processes of change were significantly different among the stages of change (all p values ＜ .05). The study findings provide guidance in designing exercise interventions to increase compliance of older persons with exercise.